Mutual Health Organizations: Lessons from 20 years of experimentation in Cameroon between 2000 and 2020 - FOUAKENG, Flaubert; NJOUMEMI, Zakariaou; ANGWAFO III, Fru; MBACHAM, Wilfred (International Journal of Scientific Research and Management (IJSRM), 2022)
The direct payments which became widespread in Cameroon in the 1990s deteriorated the problem of financial inaccessibility to the health care services and medicine. To provide a solution to this problem, the National Health Development Plan 1998-2008 and the Health Sector Strategy 2001-2015 have planned to promote Mutual Health Organizations.The present study had as objective to evaluate the experimentation process of Mutual Health Organizations in Cameroon between 2000 and 2020 and to draw lessons learn from it.The methodology was based on a literature review and information gathering in the field.The results show that the 2000-2010 period saw the number of Mutual Health Organizations increased from 9 to 158. However, this number fell from 158 to 58 between 2010 and 2014. The reasons of this failure are: Projects financing problems, managerial failure, mistrust of the population, poverty, non-adaptation of the model to the culture and difficulties to collaborate with health facilities.Due to this failure of Mutual Health Organizations, we suggest experimenting with another way of promoting them and to professionalize the management. Indeed, in the perspective of the promotion of universal health insurance covering the poor or the informal and rural sector, the study suggests to professionalize and experiment the networking of Mutual Health Organizations leaned on Organizations of mutual aid and solidarity or of the social and solidarity economy which are very wide-spread and which ally with a certain success the activities of micro-insurance (including health) to those of microcredit.